간호사의 시간압박감이 안전간호활동에 미치는 영향: 소진의 매개효과를 중심으로 - 윤정임(Yun, Jungim); 손현미(Son, Hyun-mi) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2019)
목적: 본 연구는 간호사의 시간압박감이 소진을 매개로 안전간호활동에 미치는 효과를 파악하기 위한 실시한 연구이다. 방법: 연구대상자는 2개의 대학병원에서 1년 이상 근무한 간호사 147명이다. 자료는 2017년 7월 31일부터 8월 31일까지 자가보고식 설문지를 이용하여 수집하였고, 수집된 자료는 SPSS 23.0 프로그램을 이용하여 t-test, ANOVA, and Pearson’s correlation coefficients로 분석하였다. 매개효과 검증을 위해 단계별로 단순, 복합 회귀분석을 실시하였으며 유의성은 Sobel test로 확인하였다. 결과: 시간압박감과 소진은 안전간호활동과 유의한 음의 상관관계가 있었으며, 시간압박감과 소진 간에는 유의한 양의 상관관계가 있었다. 시간압박감과 안전간호활동의 관계에서 소진의 매개효과를 확인한 결과, 간호사의 시간압박감은 안전간호활동에 유의한 영향을 미쳤고, 또한 시간압박감은 소진을 통해서도 안전간호활동에 유의한 영향을 미치는 것으로 확인되어 소진의 부분 매개효과를 확인하였다. 결론: 환자안전을 위한 간호수행을 증진시키기 위해서는 간호사의 시간압박감을 줄이기 위한 효율적 업무개선 방안이 마련되어야 한다. 또한 간호사의 시간압박감으로 증강된 소진이 안전간호활동에 영향을 미치므로 소진을 관리하기 위한 중재도 함께 적용되어야 한다. Purpose: This study was done to identify the effects of nurses’ time pressure on their safety care activities throughthe mediation of burnout. Methods: Participants, 147 nurses with at least one year of work experience in two universityhospitals were enrolled in this study. Data were collected using a self-reported questionnaire from July 31, to August31, 2017 and analyzed with t-test, ANOVA, and Pearson’s correlation coefficients. SPSS 23.0 was used for analysis. Mediating effects were examined with stepwise simple and complex regression, and statistical significance was verifiedwith the Sobel test. Results: Time pressure and burnout were significantly negatively correlated with safety careactivities, and there was a positive correlation between time pressure and burnout. Regarding the mediating effectsof burnout in the relationship between time pressure and safety care activity, time pressure had a significant effecton safety care activity both directly and indirectly through burnout, confirming a partial mediation effect of burnout. Conclusion: Strategies for enhancing work efficiency to reduce nurses’ time pressure are needed to promote safetycare activities. Furthermore, because burnout facilitated by time pressure among nurses influences their patient careactivities, interventions for burnout management must also be implemented simultaneously. KCI Citation Count: 0